Morphometric indicators of broilers fed Roystonea regia fruit meal in the ration. Technical note - Vives, Yesenia; Martínez, Madeleidy; Hernández, Yasmila (Cuban Journal of Agricultural Science, 2020)
An amount of 40 male broilers, fed Roystonea regia (Kunth) O.F. Cook fruit meal in the ration, were used to determine morphometric indicators of their gastrointestinal tract. A completely randomized design was applied with four treatments, which consisted in the inclusion of 0, 5, 10 and 15% of palm kernel meal in the diet. At 42 days, animals were weighed and sacrificed. Gizzard, caeca and accessory organs (liver and pancreas) were weighed. There was an increase of gizzard size (23.28, 26.55, 25.68 g.kg-1) and of the empty caeca (4.42, 4.31, 5.38 g.kg-1) with respect to control (P <0.05). It is concluded that the inclusion of palm kernel meal in diets for broilers increased the weight of the organs of the gastrointestinal tract, related to mechanical and fermentative digestion, which improves the use of the fibrous fraction by the animal. Keywords: poultry, alternative food, royal palm, gastrointestinal tract